Analisis Pengendalian Kualitas Produk Menggunakan Metode Statistical Process Control (SPC) Pada PT Difa Kreasi - Ningrum, Harini Fajar (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2019)
PT Difa Kreasi is a manufacturing company engaged in printing and packaging. One of the carton box packaging products produced is the angle corner. Angle corner making is carried out by the production division using a jigsaw and bending machines. Operation in this process requires a high degree of accuracy, so it is deemed necessary to implement quality control so that quality control is maintained and avoids the occurrence of fatal production defects. The author is interested in conducting research related to quality control to reduce product defects using the Statistical Process Control (SPC) method. From the study held, it was concluded that the amount of angle corner production during April 2016 was 76,151 pcs with a total of 4,402 pcs or 1.77% defects, with the most dominant type of damage being the wrong size of 46.1%, imperfect shape of 30.3%, and rough cuts of 23.6%. Based on the results of the control chart p (p-chart), it can be seen that there are still product defects that are outside the control limits, the point is fluctuating and irregular. Therefore it is necessary to make improvements regularly to achieve maximum results, for example, increasing the ability of operators by conducting training, doing preventive maintenance on machines, and others.